Comparing Price Levels across Countries Using Minimum-Spanning Trees - Hill, Robert J. (The Review of Economics and Statistics, 1999)
It is shown how a comparison of price levels across a group of countries can be made by chaining bilateral price indexes across a spanning tree. It is argued that we should use the spanning tree whose resulting multilateral price indexes are least sensitive to the choice of bilateral formula. This minimum-spanning tree can be easily computed using Kruskal's algorithm. Results obtained by chaining Fisher indexes across a minimum-spanning tree are compared with the Penn World Table.